Inequality in top performance: an examination of cross-country variation in excellence gaps across different levels of parental socioeconomic status. Issue 1 (17th February 2018) - Jacobs, Babs; Wolbers, Maarten H. J.
ABSTRACT: This article examines the extent to which parental socioeconomic status (SES) affects the likelihood of a child becoming a top-performing student, offering an international perspective by reporting this relationship in 31 developed countries. The impact of 3 important educational system characteristics (differentiation in terms of early tracking, standardisation, and private schooling) on the relationship between parental SES and top performance was determined. We employed multilevel logistic regression models on data from the Programme for International Student Assessment (PISA) 2015 ( N = 216, 980) to reveal that children with low parental SES have a lower probability of becoming a top-performing student than those with high parental SES, although this association differs between countries. The negative relationship between a disadvantaged parental background and top performance was not affected by the educational system characteristics under investigation.